Early Age Properties of Low-calcium Fly Ash Geopolymer Concrete Suitable for Ambient Curing. (2015) - Nath, Pradip; Sarker, Prabir Kumar; Rangan, Vijaya B.
Abstract: Geopolymer is a promising alternative binder to Portland cement. It is produced mostly from by-product materials such as fly ash and blast furnace slag; hence recognised as a low-emission alternative binder for concrete. Recent studies have shown that the properties of geopolymers are similar or superior to those of the OPC binder that is traditionally used for concrete. Most of the previous studies employed heat curing for setting and hardening of fly ash geopolymer mixtures. Heat curing process requires special arrangements which is energy-consuming and may not be feasible to apply in cast-in-situ concreting. Therefore, development of geopolymer mixtures suitable for curing at normal temperature will widen its application. This paper presents a study on low calcium fly ash based geopolymer concrete cured in ambient temperature (23 o C) without additional heat. Small amount of additives were added with fly ash to accelerate the early-age reaction. Setting times of geopolymer pastes, and workability and compressive strength of geopolymer mortar were studied. The effects of the additives and binder content in the mixtures were determined from experimental results. The results show that inclusion of additives with fly ash significantly enhanced the early age properties. Setting time reduced to reasonable values and compressive strength increased to enable early de-moulding of specimens. Compressive strength increased with the increase of binder content. However, workability results showed an optimum binder content for the fly ash geopolymer blended with the additives. The results suggest that suitable geopolymer mixtures can be designed for ambient curing with low calcium fly ash and the additives as partial replacement.